Agonism, Antagonism, and Inverse Agonism Bias at the Ghrelin Receptor Signaling - M'Kadmi, Céline (J Biol Chem, 2015)
The G protein-coupled receptor GHS-R1a mediates ghrelin-induced growth hormone secretion, food intake, and reward-seeking behaviors. GHS-R1a signals through G(q), G(i/o), G(13), and arrestin. Biasing GHS-R1a signaling with specific ligands may lead to the development of more selective drugs to treat obesity or addiction with minimal side effects. To delineate ligand selectivity at GHS-R1a signaling, we analyzed in detail the efficacy of a panel of synthetic ligands activating the different pathways associated with GHS-R1a in HEK293T cells. Besides β-arrestin2 recruitment and ERK1/2 phosphorylation, we monitored activation of a large panel of G protein subtypes using a bioluminescence resonance energy transfer-based assay with G protein-activation biosensors. We first found that unlike full agonists, G(q) partial agonists were unable to trigger β-arrestin2 recruitment and ERK1/2 phosphorylation. Using G protein-activation biosensors, we then demonstrated that ghrelin promoted activation of G(q), G(i1), G(i2), G(i3), G(oa), G(ob), and G(13) but not G(s) and G(12). Besides, we identified some GHS-R1a ligands that preferentially activated G(q) and antagonized ghrelin-mediated G(i)/G(o) activation. Finally, we unambiguously demonstrated that in addition to G(q), GHS-R1a also promoted constitutive activation of G(13). Importantly, we identified some ligands that were selective inverse agonists toward G(q) but not of G(13). This demonstrates that bias at GHS-R1a signaling can occur not only with regard to agonism but also to inverse agonism. Our data, combined with other in vivo studies, may facilitate the design of drugs selectively targeting individual signaling pathways to treat only the therapeutically relevant function.